Axial energy spread measurements of a 27.12 MHz multicusp ion source - Voznyi, V.I.; Miroshnichenko, V.I.; Mordyk, S.N.; Storizhko, V.E.; Shulha, D.P. (Вопросы атомной науки и техники, 2009)
A 4.7 cm diameter and 8 cm long 27.12 MHz radio-frequency (RF) inductively coupled multicusp ion source has
been designed for ion beam applications. Ion energy distribution functions (IED) of the extracted helium and argon ion
beams were measured by use of a retarding field energy analyzer. Influence of the RF power, gas pressure and the
extraction voltage on the ion energy spread of the beam is described. The ion energy spread is found to be 7 eV for
helium beam at 200 W RF power and gas pressure of 5 mTorr. Розроблено 27,12 МГц мультикаспове ВЧ- іонне джерело діаметром 4,7 см і завдовжки 8 см для іонно-
пучкових застосувань. Обмірювано функції розподілу іонів з енергії (ФРІЕ) витягнутого гелієвого та
аргонового пучків за допомогою енергоаналізатора із затримуючим полем. Розглянуто вплив ВЧ- потужності,
тиску газу та витягаючої напруги на енергетичний розкид іонів пучка. Мінімальний енергетичний розкид іонів
гелієвого пучка дорівнює 7 еВ при 200 Вт ВЧ- потужності та 5 мТорр тиску газу. Разработан 27,12 МГц- мультикасповый ВЧ- ионный источник диаметром 4,7 см и длиной 8 см для ионно-
пучковых приложений. Измерены функции распределения ионов по энергии (ФРИЭ) извлеченного гелиевого и
аргонового пучков с помощью энергоанализатора с задерживающим полем. Рассмотрено влияние ВЧ-
мощности, давления газа и вытягивающего напряжения на энергетический разброс ионов пучка. Минимальный
энергетический разброс ионов гелиевого пучка равен 7 эВ при 200 Вт ВЧ- мощности и 5 мТорр давления газа.